Indigenous Media in Latin America: Uses, Meanings and Cartographies of a Plural Experience - Orobitg, Gemma; Martínez Mauri, Mònica; Canals, Roger; Celigueta, Gemma; Gil García, Francisco M.; Gómez Ruiz, Sebastián; Izard, Gabriel; López García, Julián; Muñoz Morán, Óscar; Pérez Galán, Beatriz; Pitarch, Pedro (Revista de historia., 2021)
This article presents an analysis of the state of indigenous communication in Latin America with an ethnographic and comparative approach based on six case studies: Mexico, Guatemala, Panama, Colombia, Bolivia and Argentina. Our study deals with the situation of the «media landscapes», that is, the proliferation of technological communication media in each context, their effective social uses and their transformations over time. For this, we highlight three analytical aspects: 1) innovations in indigenous communication, which have moved from an emphasis on technological appropriation to the need for its incorporation as a cultural value, as well as a change in emphasis from «resistance» to «decolonization», 2) the characteristics that define indigenous communication, and 3) the confirmation of its heterogeneity and involvement in concrete and local social and political realities.